Impactos ambientales significativos en la Bahía de Puerto Pizarro; Tumbes 2007 - Pérez Cerquera, Santos Oswaldo (2014)
To identify and assess significant environmental impacts in the Bay of Puerto Pizarro procedures established by APHA, AWWA & WPCF (1998) for surface water samples adjacent to the landing craft of Puerto Pizarro were followed from February to December 2007. They were sampled and identified to component level gender phytoplankton and zooplankton. Likert scale one quoted by Vásquez et al,, (2007) built with 27 items, which were resolved by 50 residents of Puerto Pizarro selected No probabilistic sampling was used for convenience. Not significant, significant and very significant for both negative and positive impacts: types of environmental impacts were established. It was concluded that: 1. The amount of Total Coliforms and Thermotolerant in seawater adjacent to the Fish Landing Craft Puerto Pizarro in Tumbes area was higher than 2400 MPN / 100 mL that exceed the provisions of ACE WATER resulting in the most negatively impacted by human activities of the people of Puerto Pizarro environmental factor. 2. negative impacts, 67% were rated as very significant and 33% as significant and not insignificant negative impacts were identified. Of the positive environmental impacts, 67% were classified as significant and 33% as very significant. No insignificant 3. The highly significant negative impacts identified and prioritized reported positive impacts are: The shrimp activity, fuel sales on the banks of the bay, poor management of solid waste: the people throw trash in the bay; DPA, faucets and food outlets alter the natural landscape of the area. 4. The merchants and sellers cast solid and liquid wastes Bay; 5. The population contributes to further alter the landscape of the area.